The effect of radiation damage on the light yield and uniformity of candidate plastic scintillator tiles for the CMS hadron calorimeter upgrade - Gevorgyan, A.; Petrosyan, A.; Tumasyan, A.; Van de Klundert, M.; Van Haevermaet, H.; Van Mechelen, P.; Van Spilbeeck, A.; Alves, G. A.; Hensel, C.; Alda Junior, W. L.; Carvalho, W.; Chinellato, J.; et al. (IOP Publishing Ltd, 2025)
A study has been performed to understand the effects of radiation damage on various plastic scintillator tiles considered for a possible upgrade of the hadron calorimeter of the CMS detector. Measurements were made with unirradiated tiles and with tiles that had been irradiated in the CMS collision hall to a dose of 44 kGy. Results are presented for the tiles of different shapes in terms of the energy spectrum, efficiency as a function of the position at which each tile was hit, as well as light yield. All the tiles showed a light reduction of up to about 50%. The tiles with the shape currently used in the CMS detector did not see increased non-uniformity of light collection, while a significant disuniformity was observed for the tiles considered as alternatives.
Keywords: Calorimeters; Interaction of radiation with matter; Scintillators, scintillation and light emission processes (solid, gas and liquid scintillators); Calorimeter methods; DESIGN; Instruments & Instrumentation